The Regime of Seaports in Ukraine: A Complicated Way to Updating Legal Regulation - Andrushchenko, Sergiy; Андрущенко, С. (Одеса : Видавничий дім «Гельветика», 2020)
The article outlines the advantages and disadvantages of the current legislation of Ukraine in the field of establishing the legal regime of seaports. The documents of long-term strategic planning in the maritime sphere, international agreements and sectoral (port) legislation are analyzed. It is determined that neither the program documents of the maritime sphere of Ukraine, nor other national legislation of the port sphere contain generalized norms on the regimes of seaports, but outline their components. The first indicates the need and ways to improve them, and the second – these components are regulated in detail and clearly specified, comprehensively characterize the established regimes of seaports, but only from the standpoint of domestic law, not taking into account international (bilateral) agreements on merchant shipping. At the same time, these agreements determine one of the largest elements of the integrated regime of seaports – the regime of ships under foreign flags and the regime of their crews. The author proposes to amend the current legislation of Ukraine in the field of port activities and indicate in it the determinism of the regimes of seaports of Ukraine not only of domestic legislation but also of the rules of bilateral agreements on merchant shipping. It is also noted that such norms can be enshrined in the future law of Ukraine on inland waters, the territorial sea and the continental shelf. У статті окреслено переваги та недоліки діючого законодавства України у сфері встановлення правового режиму морських портів. Проаналізовано документи довгострокового стратегічного планування у морській сфері, міжнародні угоди та галузеве (портове) законодавство. Визначено, що ані програмні документи морської сфери України, ані інше національне законодавство портової сфери не містять узагальнених норм про режими морських портів, але окреслюють їх складники. У перших – зазначається про необхідність та шляхи їх поліпшення, а у другому – ці складники детально регламентовані та чітко конкретизовані, комплексно характеризують встановлені режими морських портів, проте лише з позицій внутрішнього законодавства, не враховуючи норм міжнародних (двосторонніх) угод про торговельне мореплавство. При цьому, саме цими угодами визначається один з найбільших елементів комплексного режиму морських портів – режим суден під іноземними прапорами та режим їх екіпажів. Автор пропонує внесення змін до діючого законодавства України у сфері портової діяльності та зазначення у ньому про детермінованість режимів морсь- ких портів України не лише внутрішнім законодавством, але й нормами двосторонніх угод про торговельне мореплавство. Також відзначається, що такі норми можуть отримати своє закріплення у майбутньому законі України про внутрішні морські води, територіальне море та континентальний шельф.
Andrushchenko S. The Regime of Seaports in Ukraine: A Complicated Way to Updating Legal Regulation / S. Andrushchenko // Lex Portus : юрид. наук. журн. / редкол. : С. В. Ківалов (голов. ред. ради), Б. А. Кормич (голов. ред.), Т. В. Аверочкіна (наук. ред., відп. секр.) [та ін.] ; НУ "ОЮА", ГО "МА Святий Миколай". – Одеса : Видавничий дім «Гельветика», 2020. - № 3. – C. 44 - 62. DOI 10.26886/2524-101X.3.2020.3
Keywords: Research Subject Categories::LAW/JURISPRUDENCE; seaport; seaport regime; development of port legislation; public administration of port activities; морской порт; режим морского порта; развитие портового законодательства; публичное администрирование портовой деятельности; морський порт; режим морського порту; розвиток портового законодавства; публічне адміністрування портової діяльності